Dunia Islam di Era Modern pada Masa Tunisia - Rahmawati, Rahmawati (Jurnal Adabiyah, 2012)
The islamization in Tunisia applied Maliki School, a sect that has existed in 8 century. Anyhow, most of ulama also adhered Asy’ariyah theology and eternalize religious tradition such Maulid ceremony, reciting sufistic rite. However, the Islamic progress in this country decreased following the political waves happening in Tunisia, notebly in Franch colony. Along the Franch protectoral, there had been two religious movement namely, traditional and modern.